The Czech Republic 2014 European Parliament Election: Voters Gone Out, New Parties In - Kaniok, Petr (Political Preferences, 2014)
This article describes and evaluates 2014 Czech European Parliament (EP) election. Starting with the context of the election, it goes through all relevant party actors participating in the election and introduces them both in general ideological terms as well as in relation towards the European integration. After results of election are discussed, the article concludes that 2014 EP election confirmed recent changes in the Czech party system - inter alia destabilization of the system as a whole, reconfiguration on its right wing and emergence of populism. Concerning the European message of the election, their results confirmed their second-order character. Key words: EP election 2014, Czech Republic, ANO 2011, party system, second order elections, ODS